I2‐Mediated Iodization/ [3+2] Cycloaddition/Nucleophilic Addition Tandem Reaction: Synthesis of Polyheterocycles Bearing Furoquinoline and Maleimide. Issue 8 (20th February 2019) - Du, Sidong; Pi, Chao; Wan, Ting; Wu, Yangjie; Cui, Xiuling
Abstract: An unprecedented metal‐free approach to polyheterocycles bearing furoquinoline and C2‐maleimide‐substituted quinoline has been developed with easily available quinoline N ‐oxides and maleimides via tandem reactions mediated by I2, including iodization, [3+2] cycloaddition and nucleophilic addition reactions. I2 acts as a halogenating agent to promote the subsequent [1, 5]‐sigma rearrangement. Two C−O bonds, three C−C bonds and a quaternary carbon center were formed in "one pot" manner. Abstract :